A major practicum report for Nenita Quality Foods Corporation, Marapangi, Toril, Davao City - Bolo, Chelo Sebio (2008)
A 288-hour plant practice was conducted at Nenita Quality Foods Corporation from April 6 to May 29, 2007. The objective was to provide the intern with adequate knowledge, exposure and training as a quality control and quality assurance officer of the different operations done in a meat processing plant. Through the plant practice, the intern was able to apply all the relevant gained from the academe. All the necessary information has been documented in this manuscript